Company's Fundamental, Technical and Prospect Analysis towards Share Investment Decision in Technology Sector Before and After COVID-19 Pandemic - Erwianti, Stella Nathasya; Widyastuti, Tri; Zulkifli, Zulkifli; Merawati , Endang Etty (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2025)
In the midst of the Covid-19 pandemic, the development of digital technology is growing rapidly and has become one of the main drivers of business transformation in various sectors, especially technology sector stocks. The difference in the development of technology sector stocks from before and after the pandemic is something that needs to be considered in investment decisions. The indicators used for fundamental analysis are CR, DER, TATO, ROE. Then for technical analysis using stock prices and for analysis of company prospects using PER and PBV. While in investment decisions using ROI and CAPM indicators. Quantitative methods are used in this study, where the data used for the period studied is the period before the pandemic, namely 2018-2019 and the period after the pandemic, namely 2021-2022. The results of this study are: 1) Fundamental analysis only CR shows a significant difference to investment decisions, while DER, TATO and ROE do not show a significant difference to investment decisions, 2) Technical analysis using stock prices shows a significant difference to investment decisions, and 3) Analysis of company prospects using PER does not show a significant difference to investment decisions while PBV shows a significant difference to investment decisions.